The Relationship between R&D Collaboration, Subsidies and Patenting Activity: Empirical Evidence from Finland and Germany - Bernd Ebersberger; Dirk Czarnitzki; Andreas Fier (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2004)
This study focuses on the impact of innovation policies and R&D collaboration in Germany and Finland. We consider collaboration and subsidies as heterogeneous treatments, and perform an econometric matching to analyze patent activity at the firm level. In general, we find that collaboration has positive effects. In Germany, subsidies for individual research do not exhibit a significant impact on patent activity, but the innovative performance could be improved by additional incentives for collaboration. For Finnish companies, public funding is an important source of finance for R&D. Without subsidies, recipients would show less patenting activity, whilst those firms not receiving subsidies would perform significantly better if they were publicly funded.
More recent version: http://hdl.handle.net/10419/24692
Keywords: H50; O38; C14; C25; 330; R&D; Public Subsidies; Collaboration; Policy Evaluation; Forschungskooperation; Forschungssubvention; Innovationspolitik; Wirtschaftspolitische Wirkungsanalyse; Patent; Deutschland; Finnland